ctDNA-based liquid biopsy reveals wider mutational profile with therapy resistance and metastasis susceptibility signatures in early-stage breast cancer patients - Atul Bharde; Snigdha Nadagouda; Manoj Dongare; Kanchan Hariramani; Madhura Basavalingegowda; Sumit Haldar; Alain D'Souza; Bhagwat Jadhav; Sangeeta Prajapati; Vikas Jadhav; Sujit Joshi; Aravindan Vasudevan; et al. (The Journal of Liquid Biopsy)
A minimally invasive analysis of plasma cell-free DNA (cfDNA) offers a genomic profiling of early-stage breast cancer (EBC), potentially identifying mutational signatures linked to metastasis and therapy resistance. In this study, paired plasma and tissue samples from 40 hormone receptor-positive (HR+) EBC patients were sequenced using a custom-designed comprehensive gene panel, OncoIndx. The genomic landscape of circulating tumor DNA (ctDNA) showed a broader mutation spectrum compared to tumor tissue DNA (tDNA), and provided reliable assessments of microsatellite instability (MSI), tumor mutation burden (TMB), homologous recombination deficiency (HRD), and loss of heterogeneity (LOH), all indicating high genomic instability. Importantly, early detection of estrogen receptor α (ESR1) mutations in ctDNA was achieved, highlighting its potential to identify patients at risk for endocrine resistance, a standard of care for HR + breast tumors. Mutations, particularly in DNA damage response (DDR) and proliferative signaling pathways (phosphatidyl inositol-4,5-bisphosphate 3-kinase; PIK3CA) suggest an increased risk of therapy resistance, pointing to opportunities for risk stratification and tailored treatment strategies in EBC. ctDNA-based liquid biopsy may provide minimally invasive comprehensive genomic analysis of EBC for identifying actionable targets and risk prediction for better disease management.